2012
DOI: 10.1371/journal.pntd.0001762
|View full text |Cite
|
Sign up to set email alerts
|

Whole Organism High-Content Screening by Label-Free, Image-Based Bayesian Classification for Parasitic Diseases

Abstract: Sole reliance on one drug, Praziquantel, for treatment and control of schistosomiasis raises concerns about development of widespread resistance, prompting renewed interest in the discovery of new anthelmintics. To discover new leads we designed an automated label-free, high content-based, high throughput screen (HTS) to assess drug-induced effects on in vitro cultured larvae (schistosomula) using bright-field imaging. Automatic image analysis and Bayesian prediction models define morphological damage, hit/non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(146 citation statements)
references
References 44 publications
5
140
0
Order By: Relevance
“…Even though efforts to develop objective and sensitive measures of Schistosoma viability-the readout in Schistosoma phenotypic screens-are ongoing, the lack of quantitative, robust, and relatively simple and quick-to-perform assays is still evident (11)(12)(13)16). This might be due to the complex nature of determining the viability of invertebrate multicellular parasites in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though efforts to develop objective and sensitive measures of Schistosoma viability-the readout in Schistosoma phenotypic screens-are ongoing, the lack of quantitative, robust, and relatively simple and quick-to-perform assays is still evident (11)(12)(13)16). This might be due to the complex nature of determining the viability of invertebrate multicellular parasites in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the handling of schistosomula allows automation, at least to a certain degree, the viability of the worms, which determines the drug's activity, is commonly assessed by microscopy. To overcome the subjectivity and complexity of microscopy, several novel techniques to determine schistosomulum viability have recently been presented, although microscopy is still the standard reference methodology (12,13,15,16). However, the phenotype and the degree of changes in the worms' morphology and motility heavily depend on the chemical nature of the drug, and in adult worms it has been shown that damaged tissues have the potential to regenerate (17,18).…”
mentioning
confidence: 99%
“…This assay achieves high levels of repeatability and low levels of intra-and inter-assay variabilities , and has significant advantages over conventional methods (such as larval development, motility and migration inhibition methods; cf. Le Jambre, 1976; Martin and Le Jambre, 1979;Dobson et al, 1986;Kotze et al, 2006;Demeler et al, 2010), particularly in terms of ease of use, accuracy of results, throughput, time and cost, and compares very favourably with other assays developed for parasitic worms (e.g., Smout et al, 2010;Marcellino et al, 2012;Paveley et al, 2012;Paveley and Bickle, 2013;Hurst et al, 2014;Storey et al, 2014).…”
Section: Screening Of Compound Librariesmentioning
confidence: 98%
“…This high-content screen (HCS) has been validated against 10,041 compounds with demonstrated congruence with visual inspection. 17 Another HCS for helminths has been developed using an automated motion-based platform. The WormAssay has been tested for use with Brugia malayi worms (a causative agent of lymphatic filariasis) and has also been demonstrated to be compatible with schistosomes, 18 indicating that it could be applicable to many macroparasites.…”
Section: Drug Discovery For Ntdsmentioning
confidence: 99%